Aplikasi Cerdas: Skrining Kesehatan Mental pada Remaja - Nenty Septiana; Nurul Kamaly; Suci Zahratul Liza; Aiza; Dinda Balqis (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2026)
Globally and in Indonesia, there is a concerning increase in the prevalence of mental health conditions like depression, anxiety, and stress (DAS) among teenagers. The dynamics of biological, behavioural, and environmental development make adolescents a sensitive age group for psychological problems. This study attempts to address this issue by describing the application of technology-based preventive and promotional techniques to raise teenagers' emotional awareness and self-regulation. The invention is a web-based program called CERDAS that attempts to facilitate the process of teenage mental health self-screening in a realistic, effective, and accessible manner. This project combines a participatory educational approach with a community service strategy. The exercise significantly improved participants' emotional awareness, their capacity to identify DAS symptoms, and their ability to use adaptive coping mechanisms on their own. These findings indicate that early detection and improved emotional regulation in teenagers have been successfully supported by digital-based interventions in conjunction with straightforward educational and psychological strategies. Because the CERDAS application is simple to use for educators, healthcare professionals, and communities that support adolescents, it may be a good way to support mental health promotion programs for teenagers.